Antibacterial activity, free radical scavenging property and phytochemical screening of Diospyros kaki fruit of Kumaun Himalayan Region, Uttarakhand - Pandey, Neelaxi; Bisht, Satpal Singh; Rana, Mahendra; Mishra, Rojita (Journal of Postharvest Technology, 2021)
Diospyros kaki is a deciduous tree found in the hills of Kumaun region up to an elevation of 1500 m , most of studies on the fruit of this plant  have been carried out in the countries like China, Japan, Myanmar, Brazil, Turkey, Italy and South Korea very less attention has been paid to  this less known wild fruit in India. This study primarily deals with total phenolic, Flavonoid, tannin content, antioxidant and antibacterial activity.  Ascorbic acid was used as standard for the evaluation of antioxidant activity. The IC50 value for ethanolic extract and aqueous extract was  recorded 50.43; 81.9 ppm respectively. Diospyros kaki fruit was found to contain significant amount of antioxidants. Antibacterial activity was  performed by disc diffusion method against the strain Salmonella typhimurium (MTCC 3224), Klebsiella pneumonia (MTCC 3384), Bacillus  subtilis (MTCC441), Aeromonas hydrophila (MTCC 646), and Pseudomonas aeriginosa (MTCC 103). This study showed that the ethanolic  extract of the fruit has significant amount of phytochemicals and antibacterial activity as compared to its aqueous extract.
Keywords: Diospyros kaki; flavonoid content; phenolics content; tannin content; c 50; antioxidant activity; antibacterial activity